SURGEONS EXPERIENCE WITH THE CONVERSION RATE OF LAPROSCOPIC TO OPEN CHOLECYSTECTOMY IN PATIENTS WITH PREVIOUS ABDOMINAL SURGERY - Kamran Hakeem Khan; Tariq Jabbar Khan; Mohammad Farid Khan; Fazal Ghani; Sidra Manzoor (Journal of University Medical & Dental College, 2019)
BACKGROUND: Laparoscopic cholecystectomy is considered a gold standard management of gall stones. Some cases are still converted into open cholecystectomy. Among many other factors, the most important factor is dense adhesions due to previous abdominal surgery. Surgical skills and experience of an operating surgeon plays a vital role in reducing the conversion rates. OBJECTIVE: We aim to determine the relation of surgeons experience with the conversion rate of laparoscopic to open cholecystectomy in patients of previous abdominal surgery. METHODS: This cross sectional study was conducted from December 2011 to December 2015. We included patients with previous abdominal surgery who were admitted with gall stone disease and planned to be operated by laparoscopic method. Those patients who have other factors responsible for conversion beside previous abdominal surgery were excluded from the study. A routine preoperative assessment, including biochemical liver assessment and abdominal ultra-sonography was performed for all patients before surgery. The preoperative data collected was age, gender, location and history of previous abdominal surgery. RESULTS: Total conversion was 11.7 %( 35/298) which was signiﬁcantly low with p-value <0.001. Conversion based on gender was found to be insigniﬁcant with p-value =0.07. CONCLUSIONS: Conversion rate of laparoscopic cholecystectomy to open cholecystectomy in patients of previous abdominal surgery can be markedly reduced if laparoscopic cholecystectomy is performed by high volume surgeon.